Shaping Community-Based Rehabilitation: Policy and Practice in Philippine Parole and Probation - Abelardo Morrok; Mark Patalinghug (Universitas Negeri Semarang, 2026)
Community-Based Rehabilitation (CBR) is increasingly positioned as a cornerstone of restorative and community-oriented corrections, yet its implementation is often assessed through offender outcomes rather than through the frontline officers who translate policy into practice. In the Philippines, empirical knowledge remains limited on how Probation and Parole Officers (PPOs) experience, negotiate, and sustain CBR work amid institutional constraints. Addressing this gap, this qualitative case study examined the lived experiences, implementation challenges, and coping mechanisms of PPOs in Region IX, Zamboanga Peninsula. Data were generated from ten experienced PPOs through in-depth interviews and focus group discussion and analyzed thematically. Findings reveal that PPOs construct CBR as both a rehabilitative duty and a moral vocation, deriving professional meaning from client transformation and successful reintegration. However, their practice is constrained by heavy caseloads, inadequate operational resources, long-distance field assignments, organizational tensions, shifting policies, and recurring ethical dilemmas. Despite these pressures, PPOs manage their work by continually re-prioritizing, managing emotion, learning, coping, and public service. The unique contribution of this study is conceptualizing CBR implementation as a human-institutional practice – rather than as a policy or client-driven practice – that is affected by the well-being, discretion, and coping capacity of officers. The study's theoretical contribution is to restorative justice and community corrections scholarship by revealing that rehabilitative results depend not only on laws and client obedience, but also on officers' emotional labor and on formal institutions' support mechanisms. The results provide directions for evidence-based improvement of support mechanisms for officers, resource distribution, and the sustainability of CBR implementation in the Philippines, and in similar correction systems.